2012
DOI: 10.5230/jgc.2012.12.3.179
|View full text |Cite
|
Sign up to set email alerts
|

18F-2-Deoxy-2-Fluoro-D-Glucose Positron Emission Tomography: Computed Tomography for Preoperative Staging in Gastric Cancer Patients

Abstract: PurposeThe use of 18F-2-deoxy-2-fluoro-D-glucose positron emission tomography-computed tomography as a routine preoperative modality is increasing for gastric cancer despite controversy with its usefulness in preoperative staging. In this study we aimed to determine the usefulness of preoperative positron emission tomography-computed tomography scans for staging of gastric cancer.Materials and MethodsWe retrospectively analyzed 396 patients' positron emission tomography-computed tomography scans acquired for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Prior reports using the Lauren classification have shown that FDG-PET/CT had significantly lower sensitivity in detecting diffuse type, SRC, and mucinous GACs than intestinal type adenocarcinomas. [9, 2427] Low iSUV as a poor prognosticator may be due to lack of avidity in diffuse type of GAC [9, 28] and low expression of glucose transporter 1 (GLUT1). [9, 25, 29]…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports using the Lauren classification have shown that FDG-PET/CT had significantly lower sensitivity in detecting diffuse type, SRC, and mucinous GACs than intestinal type adenocarcinomas. [9, 2427] Low iSUV as a poor prognosticator may be due to lack of avidity in diffuse type of GAC [9, 28] and low expression of glucose transporter 1 (GLUT1). [9, 25, 29]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the Lauren intestinal type of gastric cancer had higher 18 F-FDG uptake than the diffuse type (12,13,23,24). Low 18 F-FDG uptake in some gastric cancers may be explained by high extracellular mucin content and more dispersed and diluted tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The low spatial resolution of PET and the physiologic uptake of 18 F-FDG by benign processes such as gastritis, or simply physiologic uptake in the muscularis mucosae, make it difficult to detect early small-volume gastric cancer through a combination of partial-volume effects and high adjacent background activity. Similarly, greater depth of tumor invasion and the presence of nodal disease have been correlated with tumoral 18 F-FDG uptake (13,23,30).…”
Section: Discussionmentioning
confidence: 99%
“…7 Additionally, early gastric cancer has a very low detection rate of 20%. 19 Only 2 of the 8 gastric tumors with low affinity did not uptake FDG in our series. Five patients (8%) had stage I cancer; thus, staging had no influence on our results.…”
Section: Discussionmentioning
confidence: 52%
“…Similar rates 11,18 are usually observed in other gastric cancer studies, but lesser rates (60%) were also observed. 19 Signet ring cell and mucinous carcinomas express very low levels of GLUT-1 (glucose transporter 1) receptor and 18F-FDG uptake mostly related to this receptor's levels. 7 Additionally, early gastric cancer has a very low detection rate of 20%.…”
Section: Discussionmentioning
confidence: 99%